The Role of Testosterone in Aggression - Katherine Simpson (McGill Journal of Medicine, 2020)
This review article explores the evidence that testosterone is significantly correlated with certain forms of aggression in a number of animals, although firm evidence is lacking for humans. Studies have revealed that structures within the limbic system are particularly involved in the elicitation of aggression and are sexually dimorphic. Testosterone can exert its effects in one of two ways: either on androgen receptors after conversion to 5-alpha dihydrotestosterone or on estrogen receptors after aromatization to estradiol. It can act via genomic mechanisms to induce production of proteins or via non genomic mechanisms to modulate neural activity. Androgen and estrogen receptors are also found along neurotransmitter pathways. As such, testosterone is able to modulate levels of various neurotransmitters that show evidence of mediating effects on aggressive behaviour. In addition, recent evidence suggests that these neurotransmitters are involved in processes such as olfaction and arousal and suggestions have been put forward explaining how testosterone may modulate these processes. However there is a critical time period early in life, usually within the first few days after birth, during which testosterone exposure is essential to elicit aggression in adulthood. It is thought that testosterone and its metabolites sensitize an androgen-responsive system, while estrogenic metabolites establish the capacity to fight in response to estrogenic stimulation later in life. Despite this, testosterone is only one of a myriad of factors that influence aggression and the effects of previous experience and environmental stimuli have at times been found to correlate more strongly.